All-cause and COVID-19 mortality in Qatar during the COVID-19 pandemic - Hiam Chemaitelly; Laith J Abu-Raddad; Roberto Bertollini; Adeel A Butt; Anvar Hassan Kaleeckal; Ali Nizar Latif; Mohamed H Al-Thani; Mariam Abdulmalik; Zaina Al-Kanaani; Sandy Semaan; Asma A AlNuaimi; Sawsan AlMukdad; et al. (BMJ Global Health)
Objective To investigate all-cause mortality, COVID-19 mortality and all-cause non-COVID-19 mortality in Qatar during the COVID-19 pandemic.Methods A national, retrospective cohort analysis and national, matched, retrospective cohort studies were conducted between 5 February 2020 and 19 September 2022.Results There were 5025 deaths during a follow-up time of 5 247 220 person-years, of which 675 were COVID-19 related. Incidence rates were 0.96 (95% CI 0.93 to 0.98) per 1000 person-years for all-cause mortality, 0.13 (95% CI 0.12 to 0.14) per 1000 person-years for COVID-19 mortality and 0.83 (95% CI 0.80 to 0.85) per 1000 person-years for all-cause non-COVID-19 mortality. Adjusted HR, comparing all-cause non-COVID-19 mortality relative to Qataris, was lowest for Indians at 0.38 (95% CI 0.32 to 0.44), highest for Filipinos at 0.56 (95% CI 0.45 to 0.69) and was 0.51 (95% CI 0.45 to 0.58) for craft and manual workers (CMWs). Adjusted HR, comparing COVID-19 mortality relative to Qataris, was lowest for Indians at 1.54 (95% CI 0.97 to 2.44), highest for Nepalese at 5.34 (95% CI 1.56 to 18.34) and was 1.86 (95% CI 1.32 to 2.60) for CMWs. Incidence rate of all-cause mortality for each nationality group was lower than the crude death rate in the country of origin.Conclusions Risk of non-COVID-19 death was low and was lowest among CMWs, perhaps reflecting the healthy worker effect. Risk of COVID-19 death was also low, but was highest among CMWs, largely reflecting higher exposure during first epidemic wave, before advent of effective COVID-19 treatments and vaccines.